Sudden unexpected death in epilepsy disclosure causes anxiety in patients with epilepsy: a Chinese questionnaire survey - Pan, Yuanhang; Hu, Gengyao; Wang, Zezhi; Yuan, Na; Wei, Zihan; Li, Xia; Hou, Xiaohua; Wang, Jian; Zhang, Xinbo; Chen, Ze; Qu, Shuyi; Bao, Junxiang; et al. (Frontiers in Neurology, 2023)
Background and objective Sudden unexpected death in epilepsy (SUDEP) has been regarded as a leading cause of premature death in patients with epilepsy (PWE). Although patients, relatives and caregivers have the right to be informed of SUDEP, neurologists prefer not to release the facts for fear of associated anxiety. In the study, a Chinese questionnaire survey was carried out to elucidate effect of SUDEP disclosure on anxiety in PWE and variables determining the anxiety of patients and provided suggestions for SUDEP disclosure. Methods A survey study in China was conducted. We recruited 305 PWE from 3 tertiary epilepsy centers who attended outpatient clinic from December 2021 to February 2022. Two hundred and thirty-two PWE completed the screening evaluation, survey and Hamilton anxiety rating scale (HAMA) twice with 171 PWE completing third HAMA at follow-up. HAMA scores at baseline, T1, T2 were compared using analysis of variance and dependent samples t-test. The variables related to anxiety were screened out by univariate analysis and used for multivariate logistic regression. Result We found 127 (54.7%) among the 232 participants experienced anxiety after SUDEP disclosure. HAMA scores at T1 were significantly higher than at baseline and T2, while there was no statistical difference between baseline and T2. Medical insurance, seizure severity, and whether the PWE supported SUDEP being disclosed to their relatives and caregivers only were associated with the occurrence of anxiety. Conclusion SUDEP disclosures may cause short-term acute anxiety, but have no long-term effects in PWE. Acute anxiety caused by SUDEP disclosure may be more common in PWE with NCMI and severe seizures. Meanwhile, compared with indirect SUDEP disclosure to their relatives and caregivers, direct SUDEP disclosure to PWE reduces the risk of anxiety. Recommendations are provided to avoid anxiety caused by SUDEP disclosure.